Tinjauan Kritis Tentang Program Makan Bergizi Gratis Terhadap Produktivitas Belajar Siswa - Kevin Andreas Halomoan Tambunan; Ridha Nababan; Rimma Anisa Siagian; Roslin Naiborhu; Sintia Harianti; Jamaludin Jamaludin (Lembag, 2025)
The Free Nutritious Meal Program (MBG) is one of the leading initiatives launched by the government of President Prabowo Subianto. The main objective of this program is to address nutritional problems and improve the quality of human resources in Indonesia, with a special focus on children and pregnant women. And it is also a plan for distributing nutritious meals in schools which is expected to provide justice in education because all students have the opportunity to eat nutritious food for free. Since its announcement, the implementation plan for this program has undergone various developments. Of course, this will later have an impact on student learning outcomes. In this study or research, we use the Descriptive Qualitative research method using or through Observation, Interviews, and Documentation. The purpose of this study is to find out how the implementation of this nutritious meal program runs at SMK Negeri 6 Medan during the trial period, as well as its impact on student learning outcomes and the challenges faced in its implementation.